Cautivos del espejo de agua : signos de ritualidad alrededor del manantial Hueytlílatl, Los Reyes, Coyoacán - Declercq, Stan, 1970- (Páublicahistórica ;, 2016)
"The present book analyzes the importance of the water springs within the Mesoamerican indigenous ritual and offers an interpretation of the archaeological context of some burials located next to a spring making use of a wide iconographic, historical and ethnographic repertoire. Much on inconography. This exhibition is based on the results of the archaeological excavation carried out between 2002 and 2003 in the Hueytlílatl spring, located in Los Reyes, Coyoacán, by the Archaeological Salvage Department of INAH - of which the author was a part - and of which Several objects of ceramic and lytic, several human burials and remains of architecture came to light, mostly belonging to the Late Postclassic and Early Colonial periods." (HKB Translation)--Page [9].